Impact of Practitioner Factors on Adoption of Human Resource Analytics in the Organizations of Nepal - Chhetri, Shanti Devi; Ranabhat, Deepesh; Sapkota, Pradeep; Lamichhane, Bishwa Nath (Journal of Nepalese Business Studies, 2024)
This study intends to explore the practitioner factors that influence the adoption of HR analytics in the developing country, Nepal. Adopting a quantitative approach to research and using a self-administered questionnaire, 385 organizations were purposively sampled from various types of organization in Nepal. IBM SPSS was used for analysis of the data. The empirical results exhibit that there is a statistically significant relationship between awareness and readiness of practitioners for adopting human resource analytics. However, IT expertise/analytical skills do not have a significant relationship with the same. The study concludes that organization must prepare employees for technological changes by clearly communicating the purpose and benefits of the new technology by conducting hands-on training sessions, offering step-by-step guides, and providing continuous support. These results contribute to theory by providing insights into how practitioner-related factors, such as awareness, IT expertise/analytical skills, innovation, and readiness influence the adoption of HR Analytics enriching existing models of technology adoption in the organizational context. From a regulatory perspective, the findings can inform policy frameworks to emphasize training, skill development, and standardized guidelines, ensuring organizations in Nepal are better equipped to adopt and implement HR analytics effectively.